A case report of asymptomatic cutaneous larva migrans - David, Abhinav; Srivastava, Divyanshu (International Journal of Research in Dermatology, 2021)
Cutaneous larvae migrans or creeping eruption is a serpiginous cutaneous eruption caused by the accidental penetration and migration of animal hookworm (nematode) larvae through the epidermis and subcutaneous tissue. The infection occurs most frequently in warmer climates and is associated with pruritus and burning sensations. We report a case of 48 years old farmer with vesicular lesion on left ankle progressing into a serpiginous track on the skin surface without any characteristic symptoms. Treatment with oral and topical drugs led to successful resolution of lesions within 10 days.